Similar alpha and beta diversity changes in tropical ant communities, comparing savannas and rainforests in Brazil and Indonesia - Schmidt, Fernando A.; Ribas, Carla R.; Sobrinho, Tathiana G.; Ubaidillah, Rosichon; Schoereder, José H.; Clough, Yann; Tscharntke, Teja (Oecologia, 2017)
Local biodiversity can be expected to be similar worldwide if environmental conditions are similar. Here, we hypothesize that tropical ant communities with different types of regional species pools but at similar habitat types in Brazil and Indonesia show similar diversity patterns at multiple spatial scales, when comparing (1) the relative contribution of alpha and beta diversity to gamma diversity; (2) the number of distinct communities (community differentiation); and (3) the drivers of β-diversity (species replacement or species loss/gain) at each spatial scale. In both countries, rainforests and savannas (biome scale) were represented by three landscapes (landscape scale), each with four transects (site scale) and each transect with 10 pitfall traps (local scale). At the local scale, α-diversity was higher and β-diversity lower than expected from null models. Hence, we observed a high coexistence of species across biomes. The replacement of species seemed the most important factor for β-diversity among sites and among landscapes across biomes. Species sorting, landscape-moderated species distribution and neutral drift are potential mechanisms for the high β-diversity among sites within landscapes. At the biome scale, different evolutionary histories produced great differences in ant community composition, so the replacement of species is, at this scale, the most important driver of beta diversity. According to these key findings, we conclude that distinct regional ant species pools from similar tropical habitat types are similarly constrained across several spatial scales, regardless of the continent considered.
Keywords: Biodiversity patterns; Community composition; Formicidae; Transcontinental comparison; Spatial ecology